"Fayyumi ware": variations, imitations, and importation of an early Islamic glazed ceramic type - Williams, Gregory (AUC Knowledge Fountain, 2012)
A number of recent publications have shown that a small amount of Egyptian glazed table wares were imported throughout Palestine from the early centuries of Islam onwards. One of the oft-forgotten and least classifiable types is the problematically titled ‘Fayyumi’ ware, so-called for its supposed provenance in the Fayyum. ‘Fayyumi’ pottery was actually manufactured in Fustat (Old Cairo) and a reexamination of its many variations shows it was both influenced by Chinese-inspired Iraqi white wares and Coptic pottery traditions already extant in Egypt, warranting changes to both its name and variety of definitions. One of the issues which has plagued the discipline of Islamic Archaeology is the lack of useful typologies or published studies of Islamic ceramics. A gap in the methodological approaches and nomenclature used by art historians versus archaeologists has exacerbated this problem. Here the work of both groups is combined in order to create a comprehensive representation of the ‘Fayyumi’ material. The ceramics under study come from a range of archaeological sites from Nubia to northern Palestine, including the Mediterranean and Red Sea Coasts. This is combined with pieces in museums in Cairo and Athens, and bacini inset into the walls of churches in Italy. The result more clearly differentiates the variety of types often grouped together under the term ‘Fayyumi’, with implications for a reinterpretation of our understanding of the introduction and development of glazing techniques and styles in the early Islamic period.